Influence Perceived of Usefulness, Perceived Ease of Use, and Perceived of Trust on decisions to use the Application of Pegadaian Digital Services by Customers at PT Pegadaian (Persero) Ungaran Branch Office - Alvian Dwi Ria Ristiyantina; Endang - Sulistiyani; Taviyastuti - Taviyastuti (Politeknik Negeri Semarang, 2022)
The purpose of this study was to determine the effect of perceived of usefulness, perceived ease of use, and perceived of trust on the decision to use the Pegadaian Digital Services application by customers at PT Pegadaian (Persero) Ungaran Branch Office. The data collection methods used were interviews, observations, and questionnaires which were distributed to 100 respondents with a purposive sampling method. Data analysis methods include descriptive analysis, validity test, reliability test, classical assumption test, t test, F test, and coefficient of determination. The results showed that perceived usefulness, perceived ease of use, and perceived of trust had a positive and significant influence either partially or simultantly on the decision to use. Based on the coefficient of determination test, the value on Adjusted R Square is 0.610, which means the contribution of the independent variable to the dependent variable is 61% while the remaining 0.390 or 39% is influenced by other variables not examined in this study.